EFA dan CFA untuk pengembangan skala karakter mahasiswa bidang pariwisata - Kadek Suranata; Nyoman Ari Surya Darmawan; Wayan Eka Paramartha; Kade Satya Gita Rismawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Character measurement for prospective student tourism workers has an important role in the overall education and training of prospective tourism workers. The limited scale of characters that can be used properly and meet the criteria of a valid and realizable scale makes the study of character scale development for tourism students very important. The study aims to validate factors and constructs for character measurement in tourism students. Character scale validation involved 300 tourism student respondents in Bali, utilizing six dimensions and 24 measuring items. EFA analysis in four rounds drops four items but includes all the theoretically constructed factors. CFA results confirm that 20 items of six-character scale factors are a powerful measurement model in character construction for tourism students. Each item contributes to each strong factor and correlates with equally strong factors, forming a single continuum of the same measurement. The results of this research have an important position in the overall study that develops character measurement.